Radiative characterization of supersonic jets and shocks in a laser-plasma experiment. (18th March 2021) - Bohlin, H; Brack, F-E; Cervenak, M; Chodukowski, T; Cikhardt, J; Dostál, J; Dudžák, R; Hubner, J; Huo, W; Jelinek, S; Klír, D; Kroll, F; et al.
Abstract: The interaction of supersonic laser-generated plasma jets with a secondary gas target was studied experimentally. The plasma parameters of the jet, and the resulting shock, were characterized using a combination of multi-frame interferometry/shadowgraphy, and x-ray diagnostics, allowing for a detailed study of their structure and evolution. The velocity was obtained with an x-ray streak camera, and filtered x-ray pinhole imaging was used to infer the electron temperature of the jet and shock. The topology of the ambient plasma density was found to have a significant effect on the jet and shock formation, as well as on their radiation characteristics. The experimental results were compared with radiation hydrodynamic simulations, thereby providing further insights into the underlying physical processes of the jet and shock formation and evolution.